2017
DOI: 10.1155/2017/9074601
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intestinal Alkaline Phosphatase in Inflammatory Disorders of Gastrointestinal Tract

Abstract: Over the past few years, the role of intestinal alkaline phosphatase (IAP) as a crucial mucosal defence factor essential for maintaining gut homeostasis has been established. IAP is an important apical brush border enzyme expressed throughout the gastrointestinal tract and secreted both into the intestinal lumen and into the bloodstream. IAP exerts its effects through dephosphorylation of proinflammatory molecules including lipopolysaccharide (LPS), flagellin, and adenosine triphosphate (ATP) released from cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 95 publications
6
115
1
Order By: Relevance
“…While a significant reduction in IL‐6 and alkaline phosphatase (ALP) was observed for the GE‐RES group, GE treatment alone could reduce only ALP after the first 6 months. A reduction in ALP levels is closely associated with a decrease in inflammatory conditions . Furthermore, the inflammatory cytokines, CCL3, IL‐1β, and TNF‐α, were all found to be significantly reduced in the peripheral blood mononuclear cells (PBMCs) of participants in both treatment groups.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a significant reduction in IL‐6 and alkaline phosphatase (ALP) was observed for the GE‐RES group, GE treatment alone could reduce only ALP after the first 6 months. A reduction in ALP levels is closely associated with a decrease in inflammatory conditions . Furthermore, the inflammatory cytokines, CCL3, IL‐1β, and TNF‐α, were all found to be significantly reduced in the peripheral blood mononuclear cells (PBMCs) of participants in both treatment groups.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…A reduction in ALP levels is closely associated with a decrease in inflammatory conditions. 45,46 Furthermore, the inflammatory cytokines, CCL3, IL-1β, and TNF-α, were all found to be significantly reduced in the peripheral blood mononuclear cells (PBMCs) of participants in both treatment groups. Additionally, the modulation of inflammatory responses in both intervention groups were significantly correlated with inflammationrelated microRNAs (miRNAs) in PBMCs.…”
Section: Diabetes Obesity and Metabolic Syndromementioning
confidence: 99%
“…The use of ALP as a method for pasteurization validation underappreciates its potential biological role. Although not many studies have evaluated the biological effects of milk ALP, intestinal ALP, which was shown to have similar substrate specificity than milk ALP (Morton, ), was shown to have a protective effect against intestinal and systemic inflammation by detoxifying lipopolysaccharide (Bates, Akerlund, Mittge, & Guillemin, ; Bilski et al, ). Treatment 8, for example, was shown to efficiently reduce pathogenic bacteria while preserving up to 3 times more ALP (1,095 mU/ml) than the conventional methods of pasteurization.…”
Section: Resultsmentioning
confidence: 99%
“…Of particular concern is the use of alkaline phosphatase (ALP) as they play an important role in gut barrier's function which contribute to the degradation of excessive LPS. [14][15][16] Although multiple researches of intravenous application of ALP in sepsis and septic shock has showed their value in preventing organ dysfunction, there is still no approach for enhancing barrier function and solving the pathogeny.…”
Section: Introductionmentioning
confidence: 99%